Rapid setting behaviour analysis of different proportions in cold mix asphalt pavement - Shahnewaz, Shoaib Md.; Khairil Azman, Masri; Othman, Che Puan; Moon, Juh Yuk (IOP Publishing Ltd, 2025)
Cold mix asphalt (CMA) is well-known for its energy efficiency and environmental advantages. However, maintaining balance workability during mixing and quick setting is crucial for achieving fast fixation and early traffic opening. The purpose of this study is to explore the rapid-setting behaviour of CMA pavement that has been generated with varying proportions of emulsion (4.0%, 4.5%, 5.0%, 5.5%, and 6.0%) and a specific emphasis on the volumetric parameters effect on the final product. The study also investigates the impact that different emulsion contents have on the amount of time it takes for the material to set and the volumetric properties associated with it. These characteristics include air voids, voids filled with asphalt (VFA), and voids in mineral aggregate (VMA). The results shed light on the significant role that emulsion percentage has in attaining optimum compaction and performance. In situations where there is either an excessive or inadequate amount of content, it affects the rate of setting and durability. The findings indicate that determining appropriate proportions for CMA mixes ensures the mixtures exhibit faster setting behaviour and good volumetric properties for sustainable pavement applications.